2016
DOI: 10.2298/zipi1602339m
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of acceptance of innovative computer use in teaching mathematics among pre-service class teachers and mathematics teachers

Abstract: Innovative computer use enables the strengthening and transformation of teaching practice. Notwithstanding, numerous studies have indicated that teachers do not use computers in teaching mathematics to a sufficient extent. This study was aimed at exploring the reasons for insufficient computer use by teachers, i.e. at examining the variables which may affect the acceptance of innovative computer use in teaching mathematics. Hence, the intention to use computers in teaching mathematics in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…This study revealed that five factors, DN, PEU, PU, TC, and SN, explained 27.1% of the variance in BI using structural equation modeling. All of the hypotheses concerning the key TAM variables were supported (H1 to H3), which is consistent with previous research in a variety of educational contexts (Liu et al, 2019;Milutinović, 2016;Pynoo et al, 2012;Teo & Milutinović, 2015).…”
Section: Pre-service Teachers' Intentions To Use Technologysupporting
confidence: 89%
See 2 more Smart Citations
“…This study revealed that five factors, DN, PEU, PU, TC, and SN, explained 27.1% of the variance in BI using structural equation modeling. All of the hypotheses concerning the key TAM variables were supported (H1 to H3), which is consistent with previous research in a variety of educational contexts (Liu et al, 2019;Milutinović, 2016;Pynoo et al, 2012;Teo & Milutinović, 2015).…”
Section: Pre-service Teachers' Intentions To Use Technologysupporting
confidence: 89%
“…Only a few studies have looked at the variables that impact Serbian pre-service teachers' intentions to utilize technology to date, mainly in the mathematics classroom (Milutinović, 2016;Teo & Milutinović, 2015;Teo et al, 2017). Researchers in Serbia, as well as those in other developing countries, are interested in knowing more about the important factors in implementing technology in the classroom (Mei et al, 2018;Teo et al, 2014;Kafyulilo et al, 2015).…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…All these up-to-date tools proved to be effective not only in the foreign language and culture acquisition but in physics and mathematics as well as it results in significant increase of quantum and quality of students' knowledge. Besides it has been shown that the intention to use computers is directly predicted by dominant technological pedagogical content knowledge which seems beneficial for advancing the education (Čubril et al, 2014;Milutinović, 2016). https://doi.org/10.15405/epsbs.2020.11.03.98 Corresponding Author: Ekaterina M. Vishnevskaya Selection and peer-review under…”
Section: Resultsmentioning
confidence: 99%
“…На пороге третьего десятилетия XXI века, а особенно в сложившихся условиях дистанционного обучения остро встает проблема персонификации информационнообразовательного пространства, а именно формирования такой цифровой образовательной среды, где будут обеспечены психологическая устойчивость обучающегося, бережное отношение к его ценностным ориентирам и установкам. Как отмечают исследователи, обучающиеся, участвующие в онлайн-коммуникации с коллегами из других государств, часто сталкиваются с непредсказуемыми коммуникативными неудачами, причины которых им самостоятельно не удается идентифицировать, но которые, в свою очередь, весьма характерны для ситуации общения в мультилингвальной среде коммуникантов с различным лингвосоциокультурным опытом [17], что доказывает актуальность проводимого исследования.…”
unclassified